PENDAMPINGAN PENGEMBANGAN APLIKASI SISTEM INFORMASI TRANSAKSI DAN PERSEDIAAN BARANG DAGANGAN PADA TOKO-TOKO DI BETENG TRADE CENTRE SURAKARTA - Nurtantiono, Andri; Kurnianingsih, Heny; Hendratmoko, Christiawan; Atikoh, Azizah Nur; Nurjannah, Laely (Nindikayla Institute, 2023)
SMEs as micro businesses often have many obstacles, as happened to MSME traders at the Beteng Trade Center Surakarta. The problems faced are almost the same, namely the number of employees is limited, the work of recording transactions and inventories is carried out by existing employees and is done manually. STIE Surakarta with the Business Work Lecture program provides assistance by involving students to do internships with traders at the Beteng Trade Center. Offering and practicing the use of an application that is not paid is a solution for traders